THE GROWING MENACE OF ANTIBIOTICS MISUSE IN PAKISTAN - Shehzad, Sofia (Journal of Gandhara Medical and Dental Science, 2017)
’Use and abuse of antibiotics has longbeen recognised as a challenge confronting many developed and developing nations. While the more vigilantnations have been able toaddresstheissuethroughstrict drug controlregulations,countrieslikePakistan continuetostruggle with themenace ofimproper useofmedicines speciallytheantiinfective agents.Impact of thishazardous trendonthehealthand economyofoursocietytends togo un-noticedandthepublic, health officials aswellas media officials seem tobeeitherleastinterested orcompletely unaware of the implications involved.Antibioticsareessentialdrugswhich appear tochange, forbetter orworse,thenatureofseveraldisorders,including bowelconditions,metabolicdisordersorliver disease1.Theyare known toreduce morbidityfrom a varietyofbacterial infectionsandarepotentiallifesaversin certain floridseptic conditions suchas bacteremia and meningitis.Their inappropriate use, however has ledtodecreased efficacyandbacterialresistance, therebyundermining theirusefulpotential. Thelater effect i.e. resistance ofcertain bacterium to respondto drugs theyare usuallysusceptible to, results froma genemutationthateither protects it from the actionof the drug orneutralizesit2.Globally therehasbeen a surge ofresistant pathogensincluding methicillin resistantstaphylococcus aureus, penicillin resistantstreptococcus pneumonia andvancomycin resistantenterococci.Anymicro-organism thatsurvives anantibiotic treatmentcan multiplyand pass on its resistantproperties. Afactor responsible for this unfortunatescenarioincludes;Over-prescribing and under prescribing antibiotics by the caringphysician.Exaggerationofsymptomsbypatients togeta prescriptionofantibiotics not actually needed3Reluctance onpartof the patients to followcomplete course ofantibioticsas theyfeel better4wrongchoice of antibioticsUsingantibioticsforconditions where theyarenot indicated such asviral infections (common cold andflu like symptoms)IntheUnitedStates,according toa2013report bytheCentresforDisease Controland Prevention,atleast 2 millionpeople annually"acquireseriousinfections with bacteria thatare resistant to one ormore oftheantibiotics designedto treatthose infections."Itis estimatedthatatleast 23,000people die annuallyfromantibiotic-resistantinfections.Comparative morbidityand mortalityis muchhigherin underdevelopedand developingnations of the world.Thespectrum of resistance differsacross developed and developing countries specificto theirown circumstances5. Pneumococcalresistance towards penicillin and macrolides are the highest in Latin Americancountries, as is resistance ofSalmonella and Escherichia coli towards ampicillin and sulfamethoxazole-trimethoprim6In Pakistanas in manydeveloping countries especiallyAfrican, Asian and LatinAmerican, antibacterial drugs are grossly mis-used for reasons citedbelow;There seems tobe a culture ofselfdiagnosisandtreatmentbasedon previous experiencesDoctorsarekeen onempericaluseof antibioticswithout bothering todetermine actualsensitivity of the organismsinvolvedPrivate practitionercharginghandsome fees feel somewhatobliged to prescribehigh endantibioticsfor patient satisfaction.Trendtouseantibioticsleft overfromprevious prescriptions in favour oftheindividualor other household members. Desiring aquickrelief fromsymptoms without waitingfor final diagnosis based onappropriate investigations suchas cultures.There isa basiclackofawareness 7about theilleffects of antibiotic misuseamongstthepublic andagrowingtrendof injudicious antibiotic prescriptionbyhealthprofessional,lay person and unskilledpractitioners.Theincreasingnumber of drug-resistant infections results in:Crippling illness ordisabilityIncreasedmortality from previouslytreatable infectionsProlongedrecoveryRepeated hospitalization with increased lengthof stayMore medicalconsultationsLess effective and more-invasive treatmentsHigher costof treatmentAnumberofimportant bodies suchas the World Health Organisationand the British HouseofLords have identified the reasons for the emergenceof resistance to antimicrobialagentsandthe preventive measureswhich need to beurgentlyimplementedto curbthe spread of resistantorganisms.8It’s abouttimethatwe in Pakistan shouldstart thinkingintermsof Antibioticstewardship -i.e.appropriate use of Antibiotics.Itinvolves a multifaceted approach topreventing emergenceof antimicrobialresistancebyselecting an appropriatedrugandoptimizingitsdoseandduration to cure an infection while minimizingtoxicity9.This willhelp ensure maintaining efficacyand life spanofantibiotics. Available data suggestthatgood antibiotic stewardship reduces ratesofClostridium difficile-associated diarrhea, resistantgram-negative bacilli, and vancomycin-resistant enterococci.For anAntibioticStewardship Programme(ASP)tobeeffective, it should focus onimproving qualityofcare,reducingdrugresistance, andensuring costeffectiveness. Forimplementation of such a programme itis importantto understand and allaythe concerns of general population andhighlight thebenefitsofthe proposed changes.10There is also a need forcreating public awareness and imposingdiagnostic and therapeutic guidelines at the levelofhospitals and other healthinstitutions onlines set out below;Doctor prescription should bemandatoryfor dispensing antibiotics.Dosage regimens should be strictly adhered to forthe durationprescribed.Do away with left over antibiotics Discouragethe practice ofself diagnosis and treatmentDisregard anyprevious prescriptionsand donot takeantibiotics prescribed for anyotherpersonThe age old concept of’prevention is better than cure’should be followed bypracticing basic hygiene principles like handwashing, covering food and vegetables and keeping kitchen surface and utensils clean,atall times.Some vaccines protect againstbacterial infections, suchas diphtheriaandwhoopingcough(pertusis).Toconclude, we arealreadywitnessingadipin utilityof antibiotics inthis post antibiotic era and ifthis abuseis allowed to progress unchecked we mayfindourselves atthe mercy of dangerous infections and epidemics that we willstruggle to control,